Radio Pulse Search from Aql X-1 - Long Peng; Zhaosheng Li; Yuanyue Pan; Shanshan Weng; Wenming Yan; Na Wang; Bo-Jun Wang; Shuangqiang Wang (The Astrophysical Journal)
We present 12 observations of the accreting millisecond X-ray pulsar Aql X-1, taken from 2022 August to 2023 October using the Five-hundred-meter Aperture Spherical Radio Telescope at 1250 MHz. These observations covered both the quiescence and X-ray outburst states, as determined by analyzing the X-ray data from the Neutron Star Interior Composition Explorer and the Monitor of All-sky X-ray Image. Periodicity and single-pulse searches were conducted for each observation, but no pulsed signals were detected. The obtained upper limit flux densities are in the range of 2.86−5.73 μ Jy, which provide the lowest limits to date. We discuss several mechanisms that may prevent detection, suggesting that Aql X-1 may be in the radio-ejection state during quiescence, where the radio pulsed emissions are absorbed by the matter surrounding the system.